Behind the Times : Virginia Woolf in Late-Victorian Contexts - Corbett, Mary Jean, 1962- (Book collections on Project MUSE., 2020)
"Inspired especially by feminist scholarship on the fin de siecle, this book rereads and revises Virginia Woolf's relation to the late-Victorian past, to writing by women who were her elder contemporaries, and to feminism and feminist movements around the turn of the twentieth century"--